Pengembangan E-LKPD Berbasis Problem Solving pada Materi Titrasi Asam Basa untuk Meningkatkan Motivasi dan Hasil Belajar Peserta Didik - marsim, fitriani; Danial, Muhammad; Syahrir, Muhammad (Chemistry Education Review (CER), 2022)
This study is a development research that aims to develop E-LKPD based on Problem Solving on acid-base titration material to increase students’ motivation and learning outcomes which is valid, practical, and effective to be used. The development model used refers to Addie development model, which consists of several stages, namely analysis, design, development, implementation, and evaluation. The e-LKPD that had been developed had conducted the validation by the validator/expert and trials, it had been revised by the developer to produce a valid, practical, and effective e-LKPD. The results show that the developed e-LKPD: (1) it had validated by the expert of e-LKPD 3.31 with valid criteria. E-LKPD is stated to be practical because the practicality test related to: (1) its implementation in Problem Solving learning model is at an average value of M = 1.91 in the category (1.5 ≤ M ≤ 2.0) which means the aspects and the observed criteria are in fully implemented category; (2) the teacher's response is very positive with a percentage of 100% with very practical criteria; and (3) the students' responses are very positive with a percentage of 92.60% with very practical criteria. E-LKPD also meets the effectiveness criteria with the results: (1) increasing students' learning motivation from 69.84% to 82.73% and (2) the learning outcomes meet the effective criteria with a class completeness percentage of 81.81%.